Manajemen Kewirausahaan dalam Perspektif Al-qur’an dan Hadits - Nurmahmudi Ismail (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2023)
This Research Is A Descriptive Qualitative Research Using Library Studies Or Literature Review Methods. Literature Studies Can Be Obtained By The Author Using Primary Data Sources In The Form Of Al-Qur'an And Hadith. In addition, the author uses secondary data such as books, journals and articles. After conducting a study on entrepreneurial management in the perspective of the Qur'an and Hadith, several results were found, namely the first, that in entrepreneurship we need good management in interacting and socializing between two parties in a certain form in order to gain benefits to minimize the possibility of risks that will arise . Second, entrepreneurship in the perspective of the Koran is explained in Surat Al-Jumuah verse 10 Allah SWT orders Muslims not to be lazy after carrying out worship, but to spread out on the face of the earth and carry out activities to seek the grace of Allah SWT. Third, in the perspective of hadith, it is noted that the Prophet's success in running his entrepreneurship in various regions was inseparable from his inherent traits, namely being honest (shiddiq), highly trusted (amanah), transparent (tabligh), and creative, innovative/smart (fathanah). These qualities led him to become a professional businessman. Even so, this article can still be developed by further researchers on the aspects and values ​​of entrepreneurship in the perspective of the Koran and hadith. Keywords: Entrepreneurial Management, Al-Quran and Hadith